2007
DOI: 10.1111/j.1365-313x.2007.03257.x
|View full text |Cite
|
Sign up to set email alerts
|

The ancient subclasses of Arabidopsis ACTIN DEPOLYMERIZING FACTOR genes exhibit novel and differential expression

Abstract: SummaryThe Actin Depolymerizing Factor (ADF) gene family of Arabidopsis thaliana encodes 11 functional protein isovariants in four ancient subclasses. We report the characterization of the tissue-specific and developmental expression of all Arabidopsis ADF genes and the subcellular localization of several protein isovariants. The four subclasses exhibited distinct expression patterns as examined by qRT-PCR and histochemical assays of a GUS reporter gene under the control of individual ADF regulatory sequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(202 citation statements)
references
References 64 publications
(70 reference statements)
12
190
0
Order By: Relevance
“…S16C). This localization pattern was unexpected, as previous studies reported that ADF4 localized along AFs and throughout the nucleus (Ruzicka et al, 2007;Tian et al, 2009;Daher et al, 2011;Porter et al, 2012). Although T2 plants with GFP fluorescence showed a recovery of powdery mildew susceptibility, in T3 adf4 homozygous plants, the fluorescence intensity was very weak, particularly in mature leaves, and showed little complementation in any of the four isolated lines tested.…”
Section: Nuclear Localization and Phosphorylation Of Adf4 Are Both Immentioning
confidence: 47%
See 3 more Smart Citations
“…S16C). This localization pattern was unexpected, as previous studies reported that ADF4 localized along AFs and throughout the nucleus (Ruzicka et al, 2007;Tian et al, 2009;Daher et al, 2011;Porter et al, 2012). Although T2 plants with GFP fluorescence showed a recovery of powdery mildew susceptibility, in T3 adf4 homozygous plants, the fluorescence intensity was very weak, particularly in mature leaves, and showed little complementation in any of the four isolated lines tested.…”
Section: Nuclear Localization and Phosphorylation Of Adf4 Are Both Immentioning
confidence: 47%
“…Subclass II is further divided into subclass IIa comprising ADF7 and ADF10, which are specifically expressed in mature pollen grains, and subclass IIb consisting of ADF8 and ADF11, for which expression is limited to the root epidermal cells. ADF5 and ADF9 in subclass III and ADF6 in subclass IV are expressed in a wide variety of tissues (Ruzicka et al, 2007). As in animal cells, ADFs in plants also bind to both monomeric and filamentous actins (Tian et al, 2009;Zheng et al, 2013) and regulate the organization of AFs (Zheng et al, 2013;Henty-Ridilla et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Ruzicka et al (2007) characterized the expression patterns of the 11 Arabidopsis ADF gene family members using qRT-PCR and GUS reporter gene fusions. They show that ADF9 is expressed at low levels in a broad range of tissues during plant development, and within these tissues shows the strongest expression in rapidly dividing and/or growing cells, such as those of the root and shoot meristem, leaf margins, emerging leaves and root elongation zone.…”
Section: Discussionmentioning
confidence: 99%